2021
DOI: 10.5812/mejrh.115185
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of the Tampa Scale of Kinesiophobia Questionnaire in Individuals with Non-specific Low Back Pain

Abstract: Background: The Tampa Scale of Kinesiophobia (TSK) is considered a valid and reliable tool to assess the fear-avoidance behavior in patients. There is a valid and reliable Persian version of the TSK-17. Objectives: The present study aimed to assess the internal consistency as a measurement for the test reliability and factor (domain) validity of the Persian version of the TSK-17 to determine whether a modified form can be proposed. Methods: This study analyzed the data of 295 individuals with non-specific low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…This study's findings are in line with such benchmarks of reliability and validity. Similarly, international adaptations of the TSK, such as the Persian version, have also achieved comparable standards of reliability with a Cronbach's alpha of 0.83, proving its effectiveness in assessing kinesiophobia among patients with non-specific low back pain (20). Further supporting this global trend, studies on the TSK in languages like Spanish and Japanese have reported analogous results.…”
Section: Discussionmentioning
confidence: 71%
“…This study's findings are in line with such benchmarks of reliability and validity. Similarly, international adaptations of the TSK, such as the Persian version, have also achieved comparable standards of reliability with a Cronbach's alpha of 0.83, proving its effectiveness in assessing kinesiophobia among patients with non-specific low back pain (20). Further supporting this global trend, studies on the TSK in languages like Spanish and Japanese have reported analogous results.…”
Section: Discussionmentioning
confidence: 71%
“…The total score ranges from 17 to 68, with higher scores indicating greater fear of movement. The Persian version of the Tampa Scale has high reliability and validity for individuals with chronic pain [ 44 , 45 ]. Adherence to the treatment sessions in the telerehabilitation group will be evaluated by the calendar of the application and the sessions in which the participants will perform the exercises.…”
Section: Methodsmentioning
confidence: 99%
“…The total score ranges from 17 to 68, with higher scores indicating greater fear of movement. The Persian version of the Tampa Scale has high reliability and validity for individuals with chronic pain [ 44 , 45 ].…”
Section: Methodsmentioning
confidence: 99%
“…These measures have been validated for use amongst the chronic non-malignant pain population and are widely used in clinical settings for the treatment of chronic pain (Tan et al, 2004). The Brief Pain Inventory (α > .70), Pain Catastrophising Scale (α = .87), and the TSK (α = .95) are valid and reliable for use with LBP patients (Abedi et al, 2021;Keller et al, 2004;Sullivan et al, 1995), however reliability has not been assessed amongst persons with LLA.…”
Section: Questionnairesmentioning
confidence: 99%